2016
DOI: 10.1007/s40808-016-0136-4
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sequestration and its relation with some soil properties of East Kolkata Wetlands (a Ramsar Site): a spatio-temporal study using radial basis functions

Abstract: Determination of different environmental factors and their spatio-temporal variations is sparingly important theme in ecological science because the productivity of an ecosystem is regulated by these factors. Here in East Kolkata Wetland (EKW) through a web of canal the composite tannery effluent is discharged and these are productively used in the piscicultural and agricultural farming of this area. So, in concern of agro-piscicultural productivity it is very essential to know the present soil profile of EKW.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Sewage fed fisheries and floodplain wetlands are important fishery resources in West Bengal. East Kolkata Wetland (EKW), designated as an 'International Ramsar Site' in November 2002by Ramsar Convention (1975 (Kumar 2018), and a unique agroecosystem located at the eastern outskirt of Kolkata and comprises a series of natural and manmade wetlands (Saha et al 2013;Singha Roy & Pal 2015;Pal et al 2016). Because of a widely known attribute of EKW in the recycling of waste water in the metropolitan city Kolkata, it has been named as the 'Kidney of the city' (Vicziany et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sewage fed fisheries and floodplain wetlands are important fishery resources in West Bengal. East Kolkata Wetland (EKW), designated as an 'International Ramsar Site' in November 2002by Ramsar Convention (1975 (Kumar 2018), and a unique agroecosystem located at the eastern outskirt of Kolkata and comprises a series of natural and manmade wetlands (Saha et al 2013;Singha Roy & Pal 2015;Pal et al 2016). Because of a widely known attribute of EKW in the recycling of waste water in the metropolitan city Kolkata, it has been named as the 'Kidney of the city' (Vicziany et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…About 286 bheries (a local term of fishery pond) plays a major role in purifying the sewage of Kolkata (Kumar 2018). Wastewater in EKW is extensively used in both agriculture and aquaculture since few decades (Pal et al 2016). According to the recent reports by EKWMA (East Kolkata Wetland Management Authority) and WISA (Wetland International South Asia) 2021, around 260 fish ponds receive approximately 900 MLD (million litres per day) sewage via different canals.…”
Section: Introductionmentioning
confidence: 99%
“…A marsh-Water Environment Research, Volume 89, Number 10 -Copyright © 2017 Water Environment Federation pond-marsh design wetland treatment showed that the effectiveness of this CW system was highly dependent on soil carbon content and organic matter turnover rate, proving to be large sinks for stable C forms . Furthermore, Pal, Manna et al (2016) concluded that soil of East Kolkata Wetland (EKW) stored high quantity of carbon and composite tannery wastewater was the main contributor, and the efficiency of carbon storage of the EKW ecosystem contributes to the preservation and restoration of this sensitive ecosystem.…”
Section: Other Areas Of Considerationmentioning
confidence: 99%
“…Some of these applications are as follows. Modelling coagulant dosage in water treatment plant (Heddam et al 2011); modelling daily ET 0 (Ladlani et al 2012); sequestration of soil organic carbon (SOC) in the agricultural surface soils and bottom sediments (Pal et al 2016); spatial variability of soil organic carbon (Bhunia et al 2016); predicting the side weir discharge coefficient (Parsaie 2016); simulation of nitrate contamination in groundwater (Ehteshami et al 2016); groundwater salinity prediction , and predicting the longitudinal dispersion coefficient in rivers (Parsaie and Haghiabi 2015).…”
Section: Radial Basis Function Neural Network (Rbfnn)mentioning
confidence: 99%